Metasardic themes in the novels of Amir Taj Al-Sir - Alivi, Hossain Torfi; Khezri, Ali; Balavi, Rasoul; Pur Abed, Mohammad Javad (Journal of Arabic Language Sciences and Literature, 2023)
There have been many studies on themes, in the novel and poetry, such as the theme of death and life, and others, but rarely research has touched on the themes, and the research means that theme that enters the author’s novels, in different forms and types, once intended and sometimes is motif and often as an internal intertextuality that does not depart from The scope of the metasar, who wants to love you in the narrative text, and these themes abounded in the novels of the Sudanese writer Amir Taj Al-Sir, who wrote some of his novels in the context of the metasar, and used common themes such as magic, weather, disease, medicine, perfume and death, which broke into all his novels and narrative writings, and are a motif for his text. Narrative, however, with this difference that the crown of the secret, gave the techniques of metasardom, to have a meaning discovered by those who read all his writings. The research in this study attempts to answer two basic questions: What is the metanarrative theme in the novels of Amir Taj Al-Sir? What are the characteristics of this theme in the metasarical text? It is clear through this research that some themes were not metasardic, and they are transferred from an ordinary word to a metasardic word, and sometimes they oscillate between the two. This study relies on the descriptive-analytical approach, with a literary balance in the novels of Amir Taj Al-Sir, and discussing it as an internal intertextuality, not deviating from the main topic, which is the metasar. The Coptic, “The Caterpillar”, “366”, “Ebola 76”, “The Biography of Pain”, “The Land of Sudan”, “Mahr al-Sayah”, “Qalam Zainab”, “Weather”, “Witch Resort” and “Flowers You Eat” Fire", "A Brief Biography of Darkness" and "A Painful Part of a Tale".
Keywords: Metasard; Theme; Amir Taj Al-Sir; Novel